Clinical outcomes of curative treatment for colorectal liver metastases combined with cytoreductive surgery and intraperitoneal chemotherapy for peritoneal metastases: a systematic review and meta-analysis of current evidence - Yifeng Zou; Xi Chen; Xinzhi Zhang; Zhihong Shen; Jiawei Cai; Yingxin Tan; JingRong Weng; Yuming Rong; Xutao Lin (International Journal of Hyperthermia, 2020)
Background The optimal treatment for colorectal cancer (CRC) with synchronous peritoneal carcinomatosis (PC) and liver metastases (LM) remains controversial. We aimed to investigate clinical outcomes in patients with CRC and concomitant PC and LM who had undergone curative surgery, including resections at both metastatic sites and synchronous intraabdominal chemotherapy. Methods We searched PubMed, EMBASE, and Web of Science databases for eligible studies. Studies focusing on the clinical effects of curative surgery and synchronous intraabdominal chemotherapy for patients with CRC and concomitant PC and LM were included. Meta-analysis results were recorded as hazard ratios (HRs), risk ratios (RRs) and mean differences. Results We included 9 of 998 identified studies in the meta-analysis, involving 746 patients (221 patients with PC + LM, 525 patients with PC). Overall survival (pooled HR 1.68, 95% confidence interval [CI] 1.33–2.13, p < 0.01) and disease-free survival (pooled HR 1.82, 95% CI 1.51–2.20, p < 0.01) were both lower in patients with PC + LM. A higher recurrence rate (RR 1.22, 95% CI 1.04–1.44, p = 0.02) and major postoperative morbidity (RR 1.47, 95% CI 1.19–1.82, p < 0.01) were also observed in patients with PC + LM. Conclusion Liver resection in combination with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for patients with CRC and synchronous hepatic and peritoneal metastases may be associated with worse survival and higher morbidity compared with patients with isolated PC. More restricted patient inclusion criteria should be established to facilitate an optimal prognosis for this patient group.